Development of Tropical Fruit Bars and Assessment of its Shelf Life - Rai and Sonica Gupta, C. Ramalingam*, Prenitha Mercy I., Sweta (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Five tropical fruits are chosen to make fruit bars on three important aspects namely high nutritive value, easy availability and cost effective. These different fruit bars prepared from a new process with better textural and sensory properties are assessed for storage stability with three different packaging materials. The bars are subjected to accelerated shelf life study by varying temperature and relative humidity. Changes in the soluble solid content, pH, titrable acidity and microbiological attributes are monitored. Minimally processed fruit bars are microbial sensitive entities. The data given provide an useful tool for describing microbial spoilage and seems expandable to specific microorganisms. Microbial growth is affected by pH, storage temperature or relative humidity. The sugar content did not change during the first weeks of storage but significant small declines are observed after prolonged storage. The proliferation of mesophilic bacteria, which are dominant in the product will explain these slight depletions.